Molecular dynamics guided identification of a brighter variant of superfolder Green Fluorescent Protein with increased photobleaching resistance - Rochelle D. Ahmed; W. David Jamieson; Danoo Vitsupakorn; Athena Zitti; Kai A. Pawson; Oliver K. Castell; Peter D. Watson; D. Dafydd Jones (Communications Chemistry)
Abstract Fluorescent proteins (FPs) are a crucial tool for cell imaging, but with developments in fluorescence microscopy and researcher requirements there is still a need to develop brighter versions that remain fluorescent for longer. Using short time-scale molecular dynamics-based modelling to predict changes in local chromophore interaction networks and solvation, we constructed an Aequorea victoria GFP (avGFP) variant called YuzuFP that is 1.5 times brighter than the starting superfolding variant (sfGFP) with a near 3-fold increased resistance to photobleaching in situ. YuzuFP contained a single mutation that replaces the chromophore interacting residue H148 with a serine. Longer time scale molecular dynamics revealed the likely mechanism of action: S148 forms more persistent H-bond with the chromophore phenolate group and increases the residency time of an important water molecule. As demonstrated by live cell imaging, YuzuFP not only offers a timely upgrade as a useful green-yellow avGFP for cell imaging applications over longer time scales, but it also provides a basic scaffold for future avGFP engineering efforts.